Anesthetic management of patients with carcinoid syndrome and carcinoid heart disease: A systematic review - José Luis Iglesias-González; María Rocío López-Iglesias; José M Rodríguez-López; Agustín Díaz-Alvarez; Felipe Gómez-Caminero López; Alberto Ríos-Llorente; Francisco Santiago Lozano-Sánchez; María Pilar Sánchez-Conde (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Background (purpose): Surgery on patients with Carcinoid Syndrome (CS) and Carcinoid Heart Disease (CHD) is a challenge for anesthesiologists due to the high risk of developing Carcinoid Crisis (CC). The purpose of the study is to assess whether or not the use of octreotide as prophylaxis in the perioperative environment would decrease the incidence of CC (PEAK METHOD). We also try to identify CC's precipitating factors.  Material and methods (source): Research upon octreotide efficacy on CC prophylaxis was made on PubMed, Google Scholar, Cochrane, and web of science (WOS), from January 2010 to February 2021. We carried out a retrospective qualitative Systematic Review, which was developed in accordance with the PRISMA statement.  Results (principal findings): Eleven articles were included in the study, five of them are retrospective studies, one is a prospective study, one is a prospective case series, two are retrospective case series, one is a meta-analysis of retrospective studies, and one is a cohort study. 5 of them are retrospective studies, 1 is a prospective study, 1 is a prospective case series and finally, 1 is a meta-analysis on retrospective studies. According to Massimino, et al. 2013; Guo, et al. 2014, Condron, et al. 2016 and Condron, et al. 2019, prophylaxis with octreotide is insufficient, it does not prevent and is inefficient in preventing CC. Tapia Rico et al confirm that due to the use of octreotide as prophylaxis, 1 patient experienced CC and 6 symptoms of CS. Fouche, et al. conclude that with prophylaxis, intraoperative carcinoid syndrome (ioCS) was mostly hypertensive. For the retrospective review that Kinney, et al. carried out, it was found that 169 patients did not experience CC. In the review carried out by Woltering, et al. it was found that out of 179 cytoreductive surgeries, prophylaxis with octreotide decreased the incidence of CC, they registered only 6 cases of CC (3,4%).  Discussions and conclusions: Although octreotide constitutes the cornerstone for the prevention and treatment of CC, the current data does not support the idea that it is totally effective in preventing it.